Q: What is the solution for 3x plus y equals -2 y equals -x plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2

x = 3 and y = 2

An equation, solution x = -10

3x + 2 = 3x + 6 This is not possible.

Both of them are equations!The solution is (x, y) = (2, 1).

Related questions

2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2

x = 3 and y = 2

An equation, solution x = -10

The solution to 5 = 3x + 2 is found by first subtracting 2:3 = 3x.Then dividing by 3:x = 1.

4x + 10 + 3x = 40 - 3x 4x + 10 + 3x + 3x = 40 20x = 40 x = 2

3x + 2 = 3x + 6 This is not possible.

Both of them are equations!The solution is (x, y) = (2, 1).

3x + 6 = 12Subtract 6 from each side:3x = 6Divide each side by 3:x = 2

(2, -1)

Their graphs are.

There is one solution for x and one solution for y. The solution is: x = -1 ; y = 2

x2 + 3x - 10 = (x + 5)(x - 2) ⇒ x = -5 or 2